Sudden stops, sovereign risk, and fiscal rules - José Eduardo Gómez González; Oscar M. Valencia; Gustavo A. Sánchez (Inter-American Development Bank (IDB), 2021)
This paper studies the effect of implementing fiscal rules on sovereign default risk and on the probability of large capital ow reversals for a large sample of countries including both developed and emerging market economies. Results indicate that fiscal rules are beneficial for macroeconomic stability, as they significantly reduce both sovereign risk perception and the probability of a sudden stop in countries that implement them. These results, which are robust to various empirical specifications, have important policy implications specially for countries that have relaxed their fiscal rules in response to the Covid-19 pandemic.
Keywords: C33; F34; G15; 330; fiscal rules; sovereign default risk; sudden stops; dynamic heterogeneous panel data models